Taming the chaos: NHS professionals' perspective of using video consulting during COVID-19 in Wales. Issue 4 (24th December 2021) - Johns, Gemma; Khalil, Sara; Ogonovsky, Mike; Hesseling, Markus; Wardhaugh, Allan; Phipps, Kerrie; Williams, Jessica; Whistance, Bethan; Ahuja, Alka
Abstract : The use of video consulting (VC) in the UK has expanded rapidly during the COVID-19 pandemic. Technology Enabled Care (TEC) Cymru, the Welsh Government and Local Health boards began implementing the National Health Service (NHS) Wales VC Service in March 2020. This has been robustly evaluated on a large-scale All-Wales basis, across a wide range of NHS Wales specialities. Aims: To understand the early use of VC in Wales from the perspective of NHS professionals using it. NHS professionals were approached by TEC Cymru to provide early data. Methods: Using an observational study design with descriptive methods including a cross-sectional survey, TEC Cymru captured data on the use, benefits and challenges of VC from NHS professionals in Wales during August and September 2020. This evidence is based on the rapid adoption of VC in Wales, which mirrors that of other nations. Results: A total of 1256 NHS professionals shared their VC experience. Overall, responses were positive, and professionals expressed optimistic views regarding the use and benefit of VC, even when faced with challenges on occasions. Conclusions: This study provides evidence of general positivity, acceptance and the success of the VC service in Wales. Future research studies will now be able to explore and evaluate the implementation methods used within this study, and investigate their effectiveness in being able to achieve better outcomes through VC.